DEVELOPMENT OF CYBER-PHYSICAL SYSTEM FOR LASER-BASED CONTROLLED CLOUD SEEDING - Rai, Ankush; R, Jagadeesh Kannan (Asian Journal of Pharmaceutical and Clinical Research, 2017)
This research encompasses of developing a cyber-physical system (CPS) i.e., a system which can control the physical process of cloud formation by utilizing the LIDAR technology to modulate its frequency while directed on aerosol cloud in order to control the movement of cloud, formation and precipitation in a test bed settings. This will enable studying the detailed effects of laser induced cloud nucleation and also in modeling the cloud behavior with respect to the feedback loop between induced affect through lasers upon the aerosol cloud. This involves utilization of advanced algorithms, image processing techniques to model cloud behavior and artificial intelligence to control the laser frequency modulation and pulse count, directed or incidence angle to understand the response between laser effects on aerosol cloud. Â 